2019
DOI: 10.1016/bs.aecr.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Modelling land use dynamics in socio-ecological systems: A case study in the UK uplands

Abstract: It is well-recognised that to achieve long-term sustainable and resilient land management we needs to understand the coupled dynamics of social and ecological systems. Land use change scenarios, will often aim to understand i) the behaviours of land management, influenced by direct and indirect drivers, ii) the resulting changes in land use and iii) the environmental implications of these changes. While the literature in this field is extensive, approaches to parameterise coupled systems through integration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The validation of ecological integrity showed that the Bloemfontein Karroid Shrubland still has excellent vegetation cover (79.6 ± 15.9%), possibly due to effective protection by the FSNBG. Termansen et al (2019) indicated that vegetation cover reflects both the natural habitat health and the adaptive management responses. For example, Hesp (1991) reported that excellent vegetation cover reduces splash erosion by intercepting rainfall, decreasing the overland flow and improving the infiltration of precipitation into the soil.…”
Section: Ground-truthing the Vegetation Typesmentioning
confidence: 99%
“…The validation of ecological integrity showed that the Bloemfontein Karroid Shrubland still has excellent vegetation cover (79.6 ± 15.9%), possibly due to effective protection by the FSNBG. Termansen et al (2019) indicated that vegetation cover reflects both the natural habitat health and the adaptive management responses. For example, Hesp (1991) reported that excellent vegetation cover reduces splash erosion by intercepting rainfall, decreasing the overland flow and improving the infiltration of precipitation into the soil.…”
Section: Ground-truthing the Vegetation Typesmentioning
confidence: 99%
“…Wang, G. et al [22] established a multi-objective spatial optimization model based on land use classification results to provide land use zoning plans for municipal governments in the context of low-carbon urban development. Termansen et al [23] proposed a modeling approach for land use dynamics based on choice experiments and spatially explicit system dynamics modeling to predict trends in land use under different environmental and policy scenarios. The study of construction land expansion and the study of optimal allocation of arable land are the main objects for research.…”
Section: Introductionmentioning
confidence: 99%
“…The system-level behaviour of a CAS emerges from interactions amongst decision makers and between individual decision makers and the environment. Examples of CAS are energy markets (North et al 2002, with businesses, and electricity consumers as decision makers, within an environment composed of the power market and regulating administration), or land-use systems (Termansen et al 2019, with farmers and land managers as decision makers, and the land and its vegetation as environment).…”
Section: Introductionmentioning
confidence: 99%